Practical applicability of the method for measuring pressure of controlled medium on the example of a pulsating combustion boiler. (November 2019) - Sinitsyn, Anton; Mukhametova, Liliya
Abstract: This paper proposes a new way to study the nature of vibration component of pressure change over time for an energy device. This method makes it possible to record and process measurement results, compare frequency characteristics at various points of the device working space, and evaluate the presence of defects in its work. The authors have identified the main problems of developing a measuring complex to study the nature of vibration component of the pressure change over time for an energy device, and numerical and field tests have been carried out.